Blaustein’s humanistic psychology in a hermeneutical key - Gołaszewski, Filip (Phainomena (Ljubljana), 2025)
The article explores Blaustein’s humanistic psychology as a form of hermeneutics. In particular, I analyze Blaustein’s concept of “humanistic reality” (rzeczywistość humanistyczna) and “experiential wholes of higher order” (całości przeżyciowe wyższego rzędu) in light of Dilthey’s and Spranger’s hermeneutical ideas, taking the methodological emphasis on understanding as the background of my analyses. I argue that Blaustein’s approach to psychic life through cultural artefacts adapts a hermeneutic circle wherein individual human understanding and humanistic reality mutually constitute each other. In this respect, I discuss Blaustein’s applications of this methodology in his accounts of Goethe’s and Hebbel’s literary works. Although Blaustein never explicitly employed hermeneutical terminology, his theoretical framework incorporates three key hermeneutical elements: methodological interpretation, literature as expression of inner life, and circular understanding between parts and wholes.
Keywords: hermeneutic circle; hermeneutics; hermenevtični krog; hermenevtika; humanistic psychology; humanistic reality; humanistična psihologija; humanistična resničnost; interpretacija; interpretation